2019
DOI: 10.1007/s00392-019-01495-x
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide ecto-enzyme metabolic pattern and spatial distribution in calcific aortic valve disease; its relation to pathological changes and clinical presentation

Abstract: Background Extracellular nucleotide metabolism contributes to chronic inflammation, cell differentiation, and tissue mineralization by controlling nucleotide and adenosine concentrations and hence its purinergic effects. This study investigated location-specific changes of extracellular nucleotide metabolism in aortic valves of patients with calcific aortic valve disease (CAVD). Individual ecto-enzymes and adenosine receptors involved were analyzed together with correlation with CAVD severity and risk factors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…In line with these results, activation of the A 2A receptor promoted the mineralization process in VIC cultures by favoring the cAMP/protein kinase A pathway, while activation of the A 1 receptor resulting in decreased cAMP levels, inhibited VIC mineralization [31]. Moreover, adenosine treatment of mice aortic roots exposed to an osteogenic medium attenuated mineralization by A 1 and A 2B receptor activation, whereas the A 2A receptor had an opposite effect on aortic root mineralization [74]. Recently, an in vitro study using human aortic smooth muscle cells demonstrated that triggering the A 3 receptor resulted in a reduction in matrix mineralization, probably by decreasing alkaline phosphatase activity [75].…”
Section: Involvement Of P1 Receptors In Arterial Calcificationsupporting
confidence: 67%
“…In line with these results, activation of the A 2A receptor promoted the mineralization process in VIC cultures by favoring the cAMP/protein kinase A pathway, while activation of the A 1 receptor resulting in decreased cAMP levels, inhibited VIC mineralization [31]. Moreover, adenosine treatment of mice aortic roots exposed to an osteogenic medium attenuated mineralization by A 1 and A 2B receptor activation, whereas the A 2A receptor had an opposite effect on aortic root mineralization [74]. Recently, an in vitro study using human aortic smooth muscle cells demonstrated that triggering the A 3 receptor resulted in a reduction in matrix mineralization, probably by decreasing alkaline phosphatase activity [75].…”
Section: Involvement Of P1 Receptors In Arterial Calcificationsupporting
confidence: 67%
“…In other study, Sajjan et al showed a significant positive correlation between enhanced serum ADA levels and increase in systolic (SBP) and diastolic blood pressure (DBP) in subjects with metabolic syndrome [ 112 ]. Also our results revealed a strong positive correlation of tissue eADA activity estimated in calcified aortic valves with SBP and DBP in patients with calcified aortic valve disease [ 24 ]. There is no data elucidating the origin of elevated ADA activity in hypertension.…”
Section: Cardiovascular Pathologies Associated With Increased Ada mentioning
confidence: 93%
“…Each AR has unique cell and tissue distribution, secondary signaling transductors, affinity for adenosine, and physiological effects. In cardiovascular system, all AR subtypes were demonstrated in endothelium, vascular smooth muscle cells, cardiomyocytes, valve cells and many others [ 4 , 22 , 24 ]. A 1 R and A 3 R predominantly activate heterotrimeric G proteins belonging to the Gα i/o family, which inhibit cAMP production by adenylate cyclase, in contrast A 2A R and A 2B R predominantly activate Gαs family members, which stimulate cAMP production [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aortic valves were stained using haematoxylin/eosin (HE) and Masson's trichrome (TR) staining, as well as the previously published Orcein Martius Scarlet Blue (OMSB) protocol, to distinguish collagen, elastic lamina and smooth muscle cells and visualize atherosclerotic plaques in valves obtained from CAVD patients 22 . To distribute and localize CD38, CD73, eNPP1 and ALP protein, we used immunohistochemistry and antibody conjugated to a fluorophore (immunofluorescence) in human non‐stenotic (n = 4) and stenotic aortic valves (n = 3) as described previously 23 . Briefly, fragments of tissue were completely embedded in the OCT compound, frozen in −80°C and then cut by a cryostat.…”
Section: Methodsmentioning
confidence: 99%